2003
DOI: 10.4088/pcc.v05n0504
|View full text |Cite
|
Sign up to set email alerts
|

New Generation Antipsychotic Drugs and QTc Interval Prolongation

Abstract: Background: Recent regulatory and clinical concerns have brought into sharp focus antipsychotic drug-induced QTc interval prolongation, torsades de pointes, and sudden cardiac death. Several new generation (atypical) antipsychotic drugs have either been withdrawn from clinical use or delayed in reaching the marketplace due to these concerns. Because torsades de pointes is rarely found, QTc interval prolongation serves as a surrogate marker for this potentially life-threatening arrhythmia. Current methods of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 47 publications
0
55
1
Order By: Relevance
“…Furthermore, there are marked differences in QTc prolongation caused by different antipsychotic agents (Haddad and Anderson 2002). For example, typical antipsychotics are recognized as having a greater risk of QTc interval prolongation than are atypical antipsychotics (Vieweg 2003;Zemrak and Kenna 2008). Harrigan et al (2004) reported the effects of six antipsychotics on the QTc interval both in the absence and presence of metabolic inhibition using a prospective, randomized design.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, there are marked differences in QTc prolongation caused by different antipsychotic agents (Haddad and Anderson 2002). For example, typical antipsychotics are recognized as having a greater risk of QTc interval prolongation than are atypical antipsychotics (Vieweg 2003;Zemrak and Kenna 2008). Harrigan et al (2004) reported the effects of six antipsychotics on the QTc interval both in the absence and presence of metabolic inhibition using a prospective, randomized design.…”
Section: Introductionmentioning
confidence: 98%
“…Torsades de pointes is a rare but ominous precursor to ventricular tachycardia/fibrillation and cardiac arrest (Vieweg, 2003;Vieweg & Wood 2004) when a prolonged QT interval becomes longer than 500 ms. The QT interval represents the time from ventricular depolarization (QRS) through ventricular repolarization (T).…”
Section: Psychiatric-cardiac Disease Risksmentioning
confidence: 99%
“…Normal intervals for QT in women are described by Vieweg (2003) as between 350-450 ms. An increased risk of developing Torsades occurs when the QT is longer than 500 ms. Dysrhythmia is identified as a medication side effect, but the mechanism underlying how antipsychotics and tricyclic antidepressants lead to dysrhythmias, such as Torsades, has not been fully understood.…”
mentioning
confidence: 99%
“…Rather than attempting to develop a database that can be analyzed using parametric statistics, we employed the principles of narrative medicine in a case report format as we have in our other papers assessing psychotropic drug-induced QTc interval prolongation and TdP [Vieweg, 2003;Vieweg et al 2004;Vieweg et al 2005;Vieweg et al 2009;Vieweg et al 2012]. Data from our review of case reports in the literature and analyses of those data form the body of our paper.…”
Section: Case Report Formatmentioning
confidence: 99%